Six years of spreading BLSD skills in schools: empowering teachers as trainers - Calicchia, Sara; Capanna, Silvia; De Rosa, Mariangela; Papaleo, Bruno; Pera, Alessandra (Frontiers in Public Health, 2024)
Introduction To improve emergency response capabilities, life-saving skills should become automatic and universally acquired, starting in schools through regular, practical retraining. Teachers can serve as ideal multipliers, but effective pathways to train and motivate them are needed, as Basic Life Support and Defibrillation (BLSD) skills are not included in their academic training. This study explores innovative training solutions and facilitating factors to enhance BLSD education in schools, focusing on training and motivating teachers. Methods An in-service training program for teachers was provided and assessed in a middle school in central Italy. The study compared the skills of students trained by teachers with those trained by certified instructors, immediately after the course and six months later, through hands-on simulation. Over five years, the project expanded to three more schools. Researchers monitored classroom implementation, offering support in resolving critical issues. Results Quantitative assessments showed significant differences in student abilities immediately after the course, which diminished after six months. Teachers gained confidence and effectively taught BLSD skills. Over five years, 5,661 students were trained, with a ratio of 1 teacher for every 111 students. Sustainability factors included regular retraining, updated free materials, internal coordinators, and allowing flexibility in course delivery. Conclusion Teachers are ideal BLSD knowledge multipliers, but they require continuous training, updated educational materials, and adequate technological support to be effective. Future research should explore scaling the train-the-trainer model to larger areas, focusing on adapting it to different socio-economic contexts and overcoming organizational and motivational barriers.